1994
DOI: 10.1021/ja00097a007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Assembly of the Tyrosyl Radical-Diiron(III) Cofactor of E. Coli Ribonucleotide Reductase: 1. Moessbauer Characterization of the Diferric Radical Precursor

Abstract: The R2 subunit of Escherichia coli ribonucleotide reductase (RNR) contains a cofactor which consists of a stable tyrosyl radical ('Y 122) adjacent to a p-oxo-bridged diiron(II1) cluster. This cofactor assembles spontaneously when apo R2 is treated with Fez+ and 0 2 . By using rapid kinetic techniques, two kinetically competent intermediates in this assembly process were recently identified (Bollinger, J. M., Jr. et al. Science 1991,253,292-298). One of the intermediates is a paramagnetic iron species. By using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
304
0
2

Year Published

2002
2002
2005
2005

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(315 citation statements)
references
References 8 publications
9
304
0
2
Order By: Relevance
“…Theoretical VTVH MCD saturation magnetization data were constructed as published previously (29). Mössbauer spectra were recorded using spectrometers described previously (30). The zero velocity refers to the centroid of the room temperature spectra of metallic iron foil.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical VTVH MCD saturation magnetization data were constructed as published previously (29). Mössbauer spectra were recorded using spectrometers described previously (30). The zero velocity refers to the centroid of the room temperature spectra of metallic iron foil.…”
Section: Methodsmentioning
confidence: 99%
“…'X' has been investigated extensively using a variety of spectroscopic methods. Early investigations using Mö ssbauer spectroscopy assigned 'X' as a strongly coupled diferric iron-radical center (Bollinger et al, 1994b;Ravi et al, 1994). In a later, combined 35-GHz ENDOR and Mö ssbauer study, it was shown that 'X' is better described as a Fe III Fe IV state (Sturgeon et al, 1996).…”
Section: Functional Transient Diiron States and Radicals In The Activmentioning
confidence: 99%
“…The function of the metal site appears to be the generation and stabilization of the radical (7)(8)(9)(10). Protein R2 having the tyrosyl radical reduced to normal tyrosine is called Met-R2 (R2 Met ) and is enzymatically inactive.…”
mentioning
confidence: 99%